The influence of television content on advertisement: a neurophysiological study - Bettiga, Debora; Noci, Giuliano (Frontiers in Psychology, 2024)
Emotional and cognitive reactions to the media context prove impactful on advertising effectiveness. However, research on the topic remains lacking and with a profusion of mixed results regarding the role of the context in enhancing or detracting communication effectiveness. This study explores the media context-advertising relationship, by investigating the influence of television content on advertisement in light of media psychophysiology and grounding on the Halo effect theory. Consumers' responses to different television content and advertisements are assessed. Specifically, consumers' arousal, pleasure, attention, and memorization are measured through brain analysis, heart rate, and skin conductance detection. Self-reported methods complement such analysis, by exploring the values associated with the television content and the advertised brands. Results show that television content influences consumer responses to the advertisement and the values associated with the brands, confirming the existence of a halo effect. Responses differ among television content typologies.